Chiral luminescent lanthanide complexes possessing strong (samarium, SmIII) circularly polarised luminescence (CPL), and their self-assembly into Langmuir–Blodgett films. Issue 30 (4th July 2019) - Barry, Dawn E.; Kitchen, Jonathan A.; Mercs, Laszlo; Peacock, Robert D.; Albrecht, Martin; Gunnlaugsson, Thorfinnur
Abstract : The lanthanide directed self-assembly of chiral amphiphilicpda based ligands1 and2 with Tb III, Sm III, Lu III and Dy III salts was studied in CH3 CN solution and as SAM LB-films. Abstract : The lanthanide directed self-assembly of chiral amphiphilic 2, 6-pyridinedicarboxylic acid based ligands1 and2 with various Ln(CF3 SO3 )3 (Ln = Tb III, Sm III, Lu III, Dy III ) salts was studied in CH3 CN and evaluated with the expected 1 : 3 and 1 : 1 Ln : Ligand species forming in solution. Ligand chirality was retained and transferred, as depicted by circular dichroism (CD) and circularly polarised luminescence (CPL) measurements (for Tb III and Sm III ), to the lanthanide centre upon complexation with high dissymmetry factor values for the Sm III complexes obtained ( g lum = −0.44 and 0.29 and 0.45 and −0.23 for the 4 G5/2 → 6 H5/2 and the 4 G5/2 → 6 H7/2 transitions of Sm·1 3 and Sm·2 3, respectively). The ability of the complexes to form stable Langmuir monolayers at the air–water interface was also established while Langmuir–Blodgett films of Tb·L 3 and Sm·L 3 exhibited lanthanide luminescent emission.